Shape optimization of multi-band antennas using the coupling between microgenetic algorithms and TLM method - Chu, H. S.; Dubard, J. L.; Staraj, R. (International journal of numerical modelling, 2004)
This paper presents a new combination between transmission line matrix method (TLM) and microgenetic algorithm (µGA). This coupling is used to design patch shapes of microstrip and planar inverted—F antennas (PIFA) for broad‐band or multi‐band applications. Measured results of the µGA/TLM optimized designs show good agreement with TLM simulation. Copyright © 2004 John Wiley & Sons, Ltd.